The impact of structured education on knowledge and self-efficacy in type 2 diabetes mellitus patients - Erlin Sayuti; Hema Malini; Devia Putri Lenggogeni (PAGEPress Publications, 2024)
Patients diagnosed with Type 2 Diabetes Mellitus (T2DM) need to acquire knowledge and self-confidence to effectively engage in self-care activities. A structured education program has the potential to influence knowledge, self-efficacy, and self-care behavior. This study aimed to investigate the impact of education on the knowledge, self-efficacy, and self-care of individuals with T2DM. The research employed a quasi-experimental non-equivalent control group design with purposive sampling. The total sample size consisted of 60 participants, with 30 in each group. The intervention group attended a four-session T2DM structured education program conducted by internal medicine specialists, nurses, nutritionists, and pharmacists, while the control group continued with their usual monthly check-ups. The results of the independent t-test revealed differences in knowledge, self-efficacy, and self-care between the intervention and control groups in the post-test assessment. Education for T2DM patients was found to be effective in enhancing knowledge (p-value=0.000), self-efficacy (p-value=0.000), and self-care (p-value=0.000), making it a recommended component of self-management education to prevent complications. The implications of this study may assist hospitals in developing Standard Operating Procedures (SOPs) for implementing structured education programs for individuals with Type 2 Diabetes Mellitus as a means of enhancing patients' management skills for T2DM.